Long‐term efficacy of SGLT2 inhibitors for elderly patients with acute decompensated heart failure: The OASIS‐HF study - Amioka, Michitaka; Kinoshita, Hiroki; Fuji, Yuto; Nitta, Kazuhiro; Yamane, Kenichi; Shokawa, Tomoki; Nakano, Yukiko (ESC Heart Failure, 2025)
Aims Sodium‐glucose cotransporter 2 inhibitors (SGLT2i) have been widely demonstrated to reduce the risk of cardiovascular death and heart failure (HF) hospitalization, regardless of left ventricular ejection fraction (LVEF). However, data on the extent to which rehospitalization is suppressed following HF hospitalization are limited. This study investigated the effects of SGLT2i on rehospitalization and cardiovascular death. Methods and results The OASIS‐HF study, a multicentre, prospective observational cohort study, enrolled 361 patients aged ≥75 years hospitalized for acute decompensated HF. The impact on composite events of HF rehospitalization or cardiovascular death and the number of annual rehospitalizations were evaluated between the conventional medical therapy and SGLT2i groups. The change in eGFR slope at the 1‐year mark after the initiation of treatment in both groups was also assessed. Over an average follow‐up period of 24.9 months, composite events occurred in 70 (35.4%) of the conventional therapy group and 36 (22.1%) of the SGLT2i group (log‐rank: P = 0.016). The average number of rehospitalizations for HF per year was 0.22 ± 0.13 vs. 0.14 ± 0.08, respectively (P = 0.019). The change in eGFR over 1 year was significantly slower in the SGLT2i group compared with the conventional group (−3.55 ± 8.46 vs. −1.42 ± 7.28 mL/min/1.73 m2, P = 0.025). Conclusions The SGLT2i are not only associated with the reduction of the composite events of HF rehospitalization or cardiovascular death and protect against worsening renal function but also with a decrease in long‐term repeated HF rehospitalizations.